The Hazards of Abdominal Obesity - Seyedeh, Nasim Habibzadeh (International Journal of Global Health, 2020)
Abdominal obesitywith a big belly is one of the worse type of morbid obesity that is associated with different health failure outcomes. Central obesity leads to an increased risk of health complications such as metabolic syndrome, hypertension, insulin resistance,type 2 diabetes, heart disease and various cancers. Abdominal obesity also can specifically cause to spinal nerve pain and backache. Depression and disability are other subsequent hazards of central fatness. More importantly ,excessive central body fat ultimately contributes in all-causes of early mortality. In regards to this, individuals with abdominal obesity is urgently needed to reduce central obesity using behavior modifications. Changes in diet and performing some exercise in everyday living are essential steps.
Keywords: Abdominal fatness; Risks; Clinical problems; Morbidity